2004
DOI: 10.1002/mds.20240
|View full text |Cite
|
Sign up to set email alerts
|

Postural tremor in Wilson's disease: A magnetoencephalographic study

Abstract: The following study included 5 Wilson's disease (WD) patients showing a right-sided postural forearm tremor (4-6 Hz) and addressed the question of whether the primary motor cortex (M1) is involved in tremor generation. Using a 122-channel whole-head neuromagnetometer and surface electromyogram (EMG), we investigated cerebromuscular coupling. Postural tremor was observed in a sustained 45-degree posture of the right-sided forearm. Data were analyzed using dynamic imaging of coherent sources (DICS), revealing ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…Our current findings revealed a spatially distributed cerebello–thalamo–cortical network at tremor or double tremor frequency in WD postural tremor generation, including S1/M1, higher cortical motor areas (PM, SMA), PPC, and thalamus contralateral to the forearm tremor as well as ipsilateral cerebellum. We revealed coupling between S1/M1 and peripheral tremor in the first place,11 whereas the majority of other cerebral sources have not been consistently coherent with the tremor EMGs. Because of this lack of cerebro–muscular coherence, our CTC network findings cannot be explained by independent coupling of the different brain areas with the tremor EMGs.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Our current findings revealed a spatially distributed cerebello–thalamo–cortical network at tremor or double tremor frequency in WD postural tremor generation, including S1/M1, higher cortical motor areas (PM, SMA), PPC, and thalamus contralateral to the forearm tremor as well as ipsilateral cerebellum. We revealed coupling between S1/M1 and peripheral tremor in the first place,11 whereas the majority of other cerebral sources have not been consistently coherent with the tremor EMGs. Because of this lack of cerebro–muscular coherence, our CTC network findings cannot be explained by independent coupling of the different brain areas with the tremor EMGs.…”
Section: Discussionmentioning
confidence: 72%
“…In all patients, contralateral primary sensorimotor cortex demonstrated strongest cerebro–muscular coupling to right‐sided tremor EMG 11. The majority of other cerebral sources revealed no consistent significant cerebro–muscular coherence.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Is there any correlation between the abnormalities in diffusion images and the clinical symptoms? Magnetoencephalographic data of symptomatic patients of WD have been published and demonstrated involvement of a cerebello-thalamo-cortical network in WD tremor generation [6, 30]. Sudmeyer et al showed strongly significant correlation between unified Parkinson's disease rating scale part III action tremor score and MRI signal change ratio in the head of the caudate nucleus, the globus pallidus, and the substantia nigra in patients of WD [10].…”
Section: Discussionmentioning
confidence: 99%